Analysis of Energy Saving Opportunities In Building A Regional Secretariat of Central Java Province and The Suitability of Green Building Criteria - Bayu, Handoko; Windarta, Djaka; Hadiyanto, Hadiyanto (Green Publisher Indonesia, 2022)
The government through Law No. 30 of 2007 concerning Energy, seeks to manage the energy sector in Indonesia in a fair and equitable manner and provide benefits to all Indonesian people. The pattern of energy consumption which increases every year in line with the increase in population illustrates that a concerted effort is needed to increase the reliability of energy supply. This research is a quantitative research conducted by processing secondary data and observing on site to determine patterns of energy consumption, recommendations for energy saving opportunities and suitability of green building criteria . In this study, to obtain data regarding the condition of electricity in Building A of the Regional Secretariat of Central Java Province, primary data and secondary data were collected. Primary data was obtained from the results of a survey that was carried out in Building A of the Regional Secretariat of Central Java Province by collecting data on the type of Air Conditioner (AC) load and the lights used, data regarding the building envelope and measuring the intensity of light in each room which was assisted by a measuring instrument. Smart Sensor AS803 Digital Lux Meter